Digital health intervention for enhancing self-perceived and compliance with anti tuberculosis treatment - Fenita Purnama Sari Indah; Ayatun Fil Ilmi; Tri Okta Ratnaningtyas (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2022)
Background: Pulmonary tuberculosis is a global health problem that has become a global concern for the last two decades. One-third of the world's population has been infected with pulmonary tuberculosis. This causes pulmonary tuberculosis to become the second leading cause of death from infectious diseases in the world after Human Immunodeficiency Virus (HIV)/AIDS.Purpose: To analyze the effectiveness of digital health intervention for enhancing self-perceived and compliance with anti-tuberculosis treatmentMethod: This study uses a quantitative approach. This research is pre-experimental research with one group pretest and posttest design. In this study, respondents were given treatment using the ‘Ayo DOTS’ (Directly Observed Treatment Short-course) application. The intervention was carried out within 4 (four) weeks. Every week the respondents were given twice interventions. Posttest 1 for knowledge, perception, and practice of adherence to TB medication was conducted after 2 weeks of intervention, while posttest 2 was conducted after 4 weeks of intervention. The sample in this study were all TB patients at Pamulang Health Center, Serpong 1 Health Center and Bambu Apus Health Center who were willing to become research respondents, as evidenced by filling out the informed consent that had been given, a sample of 33 TB patients.Results: There are differences in knowledge, self-perception and adherence to taking TB drugs between pre test and post test 1 with the application of ‘Ayo DOTS’ (Directly Observed Treatment Shortcourse) p value <0.05. Similarly, the results of post test 1 and post test 2 show differences in knowledge, self-perception and adherence to taking TB medication between post test 1 and post test 2 with the application of 'Ayo DOTS' (Directly Observed Treatment Shortcourse).Conclusion: The implementation of the application ‘Ayo DOTS’ (Directly Observed Treatment Shortcourse) intervention is effective in increasing knowledge, self-perception and adherence to taking TB drugs in TB patients.